2021
DOI: 10.3389/fphar.2021.652716
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cross-Linked Hemoglobin-Based Oxygen Carrier, YQ23, Extended the Golden Hour for Uncontrolled Hemorrhagic Shock in Rats and Miniature Pigs

Abstract: Background: Hypotensive resuscitation is widely applied for trauma and war injury to reduce bleeding during damage-control resuscitation, but the treatment time window is limited in order to avoid hypoxia-associated organ injury. Whether a novel hemoglobin-based oxygen carrier (HBOC), YQ23 in this study, could protect organ function, and extend the Golden Hour for treatment is unclear.Method: Uncontrolled hemorrhagic shock rats and miniature pigs were infused with 0.5, 2, and 5% YQ23 before bleeding was contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…The vital organ functions were observed with hemorrhagic shock in 348C hot environment. The results showed that hemorrhagic shock led to vital organ function damage in room temperature environment similar with previous studies (12). It was shown that CO, CI, and SI were decreased and AST, ALT (liver damage parameter), BUN, Crea (kidney damage parameter) were increased significantly.…”
Section: Changes Of Organ Function In Rats Following Hemorrhagic Shoc...supporting
confidence: 86%
“…The vital organ functions were observed with hemorrhagic shock in 348C hot environment. The results showed that hemorrhagic shock led to vital organ function damage in room temperature environment similar with previous studies (12). It was shown that CO, CI, and SI were decreased and AST, ALT (liver damage parameter), BUN, Crea (kidney damage parameter) were increased significantly.…”
Section: Changes Of Organ Function In Rats Following Hemorrhagic Shoc...supporting
confidence: 86%
“…The resulting cross-linked tetramers were produced in a high yield and were isolated and characterized [136], but we are not aware of successful clinical trials employing these derivatives. Remarkably, YQ23, a bovine-derived cross-linked Hb, more resistant to oxidation, with a low Hb + content (<4.8%) and P50 = 40 mmHg, was tested in rats and pigs, with favorable outcomes in terms of hypotensive resuscitation, stabilized hemodynamics, an increased tissue O 2 consumption, increased cardiac output, and reduced liver and kidney injury [137], but we are not aware of any clinical trials performed with this HBOC.…”
Section: Stabilizing the Hb Tetramersmentioning
confidence: 99%
“…[21] To address these challenges, strategies to increase the molecular diameter of the HBOC and limit free hemoglobin in circulation have become requirements in the design of modern HBOCs. These strategies include chemical cross-linking of hemoglobin, [22,23] polymerization of hemoglobins, [24][25][26] and encapsulation of hemoglobin in liposome and nano-and microparticle systems. [27,28] Liposome encapsulated hemoglobin's have demonstrated many of the desired design criteria for an alternative oxygen carrier, including an absence of blood group antigens and blood-borne pathogens, and a prolonged storage capacity.…”
Section: Introductionmentioning
confidence: 99%